Level of knowledge of Stereotypic Movement Disorders among paediatric population. An update on proper differential diagnosis and management including physical exercise approach - comprehensive literature review - Jachymek, Anna; Gmitrzuk, Julia; Malinka, Zuzanna; Wiśniewska, Katarzyna; Opatowska, Martyna; Jakubiec, Joanna; Kucharski, Tomasz; Piotrowska, Marta (Quality in Sport, 2024)
Stereotypies stand out as the most debated aspect within the spectrum of repetitive behaviors observed in childhood, which encompass mannerisms,habits, compulsions, tics, and other sudden movements. Stereotypies refer to a repetitive, persistent, often rhythmic pattern of non-purposeful motor actions that may disrupt social interaction, academic performance, or other daily activities, and can potentially lead to physical harm. Many young children exhibit stereotyped behaviors, such as thumb sucking. In older children and adults, repetitive behaviors like finger tapping or drumming, self-stimulatory actions (e.g., masturbation) or leg shaking, may occur in response to boredom. These behaviors differ from Stereotyped Movement Disorder because they do not significantly interfere with daily activities nor cause self-inflicted bodily injury severe enough to warrant independent clinical attention. Stereotyped movements are commonly categorized into two groups: primary and secondary, based on the presence of additional signs or symptoms. The former are perceived as physiological, as opposed to the latter, which are considered pathological. There is growing evidence supporting a neurobiological mechanism despite some perceiving stereotypic movements as behaviors aimed at modifying arousal states. Both behavioral and pharmacological treatments have been employed with mixed results, hence, there is a need for further research in this area, including physical exercise. Conclusively, a more profound comprehension of the underlying risk factors and biology of motor stereotypies will eventually bring us nearer to developing more effective targeted therapies, which will alleviate the suffering of children who are affected.